The Effect of Using Digital Information Resources on Fulfilling the Information Needs of UIN Jakarta Library Science Students - Muzhaffar, Mohamad Miqdad Jihad; Rianti, Fahma (Librarianship in Muslim Societies, 2025)
This study aims to determine how much influence the use of digital information sources has on fulfilling the information needs of UIN Jakarta Library Science study program students class of 2020. This study uses a quantitative method with an associative approach by collecting data through  distributing  questionnaires.  Respondents  of  this  study  are  60  students  of  the  2020 Library Science study program who used digital information sources as a reference in doing coursework  with  an  accidental  sampling  technique.  This  study  uses  validity  and  reliability instrument  tests,  classical  assumption  tests  which  include  normality,  heteroscedasticity,  and linearity  tests,  as  well  as  simple  linear  regression  analysis  tests,  T-tests,  and  partial determination coefficient tests to analyze data. The uses and gratification theory is applied in this study  to  examine  how  and  to  what  extent  the  media  can  satisfy  the  audience's  demands. According  to  the  findings,  students'  ability  to  meet  their  coursework  information  needs  is impacted  by  using  digital  information  sources.  The  impact  of  accessing  digital  information sources on meeting students' information demands for coursework is very significant, as seen by the 73.2% influence given and the 26.8% influenced by other aspects not evaluated. The results of  hypothesis  testing  indicate  that  students'  information  demands  are  met  by  using  digital information sources.